PERLINDUNGAN HUKUM PENCIPTA LAGU BERDASARKAN SISTEM PEMBAYARAN FLAT PAY DAN ROYALTI TERHADAP KARYA MUSIK DAN/ATAU LAGU DI PLATFORM STREAMING MUSIK - Levyno Rahardja, Matthew; Anita Sinaga, Niru (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
The existence and payment system of royalties does not always benefit the songwriter, often the songwriter is disadvantaged by not getting royalties but his work is used and listened to either for commercial or entertainment. The flat pay payment system can interfere with the songwriter's copyright because the songwriter will not receive royalties for the use of the song's musical work on the music streaming platform. then there are several problems that raise questions, namely how the payment mechanism of the flat pay system and royalties for songwriters against musical works and / or songs on the music streaming platform and how the legal protection of songwriters against the flat pay payment system and royalties on the music streaming platform. Objectively, it aims to find out the payment mechanism and protection of songwriters against flat pay and royalty systems and subjectively add in-depth knowledge in intellectual property law. This research was conducted using the normative juridical method with primary and secondary legal sources from the literature. The flat pay system can be interpreted as a royalty payment as a whole or in full for the copyrighted work of the song while royalties are a form of compensation given to the copyright owner of the producer who promotes the copyrighted work of the creator. Legal protection of streaming music can be interpreted as an act to protect the rights of creators to work on songs contained in digital music services. It can be concluded that the payment mechanism for songwriters on the music streaming platform can be a flat pay and royalty payment system. The legal protection of songwriters in Indonesia is regulated in the Law of the Republic of Indonesia Number 28 of 2024 concerning Copyright.